Tanggap Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis hypogea L.) Terhadap Pemberian Abu Sekam Padi Pada Lahan Rawa Lebak - Mahdiannoor Mahdiannoor (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
Peanuts (Arachis hypogea L.) is classified as crops and plants rapidly produce . Lebak wetlands agroecosystem areas, which are grouped into marginal land in Kal-Sel with various efforts can be utilized for crops.Giving rice husk ash is used to loosen the soil so plant roots can make it easier to absorb nutrients in it . This study aims to ( i ) determine the growth and yield response of peanut to the application of rice husk ash on lebak wetlands , and ( ii ) to obtain the best dosage of rice husk ash growth and yield of peanut in lebak wetlands . The experiment was conducted in the Babirik Hilir Village,  Babirik District, Hulu Sungai Utara Regency in June to September 2012, using a randomized block design (RBD ), with 5 treatments and 4 replications, and 12 plants each contained 240 beds making the overall plant . Factors tested were various dosage of rice husk ash that a0 = 0 t.ha-1 ( 0 kg.plot-1) , a1 = 6 t.ha -1 ( 0.576 kg.plot-1), a2 = 12 ton.ha-1 ( 1.152 kg.plot-1) , a3 = 18 t.ha-1 ( 1.728 kg.plot-1) , a4 = 24 t.ha-1  ( 2,304 kg.plot -1) . The results showed that treatment of rice husk ash dose had no effect on plant height age 14 day Rafter pelanting (DAP), the number of leaves age 14, 21, and 28 DAP . And significant effect on plant height age 21 DAP , plant fresh weight of pods and weight of 100 seeds , and very significant effect on plant height age 28 DAP , age of the plant when the first flowering and number of pods per plant . The best treatment was found on treatment at a4 dosage of 24 t.ha -1 ( 2,304 kg.plot-1).